Lowering the recommended age for the free and active offer of influenza vaccination in Italy: clinical and economic impact analysis in the Liguria region. Issue 5 (4th May 2021) - Trucchi, Cecilia; D'Amelio, Marco; Amicizia, Daniela; Orsi, Andrea; Loiacono, Idalba; Tosatto, Roberta; Piazza, Maria Francesca; Paganino, Chiara; Pitrelli, Andrea; Icardi, Giancarlo; Ansaldi, Filippo
ABSTRACT: Objective: we estimated the epidemiological and budget impact of lowering the recommended age for influenza immunization with quadrivalent vaccine actively offered and administered free of charge to persons over 50 years old by public immunization services. Methods: a multi-cohort, deterministic, static Markov model was populated by real-world data on the clinical and economic impact of Influenza-Like Illness and Lower Respiratory Tract Infection over 1 year. Four scenarios featuring different vaccine coverage rates were compared with the base case; coverage rates in subjects with and without risk factors were considered separately. Results: compared with the base case, adopting scenarios 1–4 would reduce the annual number of influenza cases by 6.5%, 10.8%, 13.8% and 3.4%, Emergency Department accesses by 10.7%, 9.1%, 15.4% and 4.6%, complications by 8.9%, 9.9%, 14.7% and 4.1%, and the hospitalization of complicated cases by 11%, 9.1%, 15.4% and 4.5%, respectively. The four scenarios would require an additional investment (vaccine purchase and administration) of €316, 996, €529, 174, €677, 539, and €168, 633, respectively, in comparison with the base case. Scenario 1 proved to be cost-saving in the 60–64-year age-group. The incremental costs of implementing the other hypothetical scenarios ranged from 2.7% (scenario 4) to 13.2% (scenario 3). Conclusions: lowering the recommended age for influenza vaccination to 60 years would allow a high proportion of subjects at risk for severe influenza to be reached and would save money. PLAIN LANGUAGE SUMMARY: What is the context? In most European countries, influenza vaccination recommendations are age-based and thus cover individuals over 50, 60 or 65 years of age. In Italy, the age limit is 65 years. Several studies have shown that influenza vaccination in people aged between 50 and 64 years can be cost-effective, or even cost-saving. What is new and what is the impact? We assessed the effect of lowering the age limit of the vaccination recommendation from 65 to 50 years on disease burden and the budget of the healthcare payer in the Liguria region (Italy). We found that covering a higher number of subjects at risk for influenza would reduce the number of cases of illness, emergency department accesses, complications and hospitalizations. In addition, there could be significant savings for the payer.